Detection and Classification of Genetic Acute Myeloid Leukemia Cells using Deep Learning Techniques - Patel, Hema; Shah, Himal; Patel, Gayatri; Patel, Atul (International Research Journal of Multidisciplinary Technovation, 2025)
Acute Myeloid Leukemia (AML) is a hematological disease that is defined by the fast growth of aberrant myeloid precursor cells in the blood and bone marrow, which disrupts normal hematopoiesis. Treatment and prognosis are influenced by the early detection of this deadly illness and its appropriate classification. Therefore, utilizing the Human Leukemia Cytomorphology Collection dataset, which comprises leukemic and normal single-cell images of Acute Myeloid Leukemia (AML) type, this research suggests a deep learning-based hybrid model for automated leukemia detection and classification. By taking morphological characteristics and genetic abnormalities into account, leukemic cells have been distinguished. The features in this study are extracted using MobileNetV2, ResNet-101, and VGG-16. Then, feature-level stacking is performed using the Support Vector Machine and Random Forest classifiers for final classification using Principal Component Analysis (PCA). Utilising image segmentation, normalisation, data augmentation, and data oversampling techniques, the pipeline improves data quality and corrects class imbalance. Additionally, t-distributed Stochastic Neighbour Embedding (t-SNE), which shows the extracted features used for the detection of leukemia subtypes, and Gradient-Weighted Class Activation Mapping (Grad-CAM) images help with interpretability by highlighting important decision areas. The suggested study achieved 98.35% accuracy, 95.87% precision, 95.84% sensitivity, 98.97% specificity, and 95.74% F1-Score. Along with the trial results, a comparison of the four separate frameworks, viz., MobileNetV2, ResNet-101, VGG-16, and Vision Transformer, has also been carried out. The comparison shows that the proposed model outperforms the other frameworks. The outcomes show that the suggested model has the capability to be used a reliable means for the prompt identification of AML and its subtypes.